Sunscreen Use in Populations of Colour: A Comprehensive Review of Barriers, Efficacy, and Clinical Recommendations - Sarah Qanita Edwar; Devi Arofah; Irma Bernadette; Lili Legiawati; Sondang P. Sirait; Ika Anggraini; Shannaz Nadia Yusharyahya (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2025)
Populations with skin of colour (Fitzpatrick types IV–VI) have higher melanin levels, providing intrinsic photoprotection equivalent to SPF ~13.4 versus ~3.3 in lighter skin. Despite this advantage, darker skin remains susceptible to UV-related harm, including post-inflammatory hyperpigmentation (PIH), photoaging, and delayed skin cancer diagnosis. This review synthesizes evidence on sunscreen use in populations of colour, focusing on formulation efficacy, clinical outcomes, adoption barriers, and best-practice recommendations. Evidence consistently supports broad-spectrum sunscreens with SPF ≥30 for all skin types. Tinted sunscreens containing iron oxides are particularly effective against visible light–induced pigmentation, reducing blue light exposure by up to 86% and preventing PIH in 98–100% of cases. However, adoption is limited by higher costs (tinted products averaging $24.59/oz vs. $6.85/oz), restricted shade ranges, and cultural misconceptions about skin cancer risk. Only 15.79% of African American individuals report regular sunscreen use, and 76% perceive their risk as low or none. Emerging data also indicate increased photoaging risk in high–sun exposure coastal settings, including Jakarta. Optimal photoprotection for Fitzpatrick V–VI includes SPF 30 sunscreen, antioxidants, emollients, and iron oxide formulations. Effective interventions must address educational, cultural, and structural barriers while improving affordability and shade inclusivity.